Impact of commercial cigarette smoke condensate on brain tissue co-cultured with astrocytes and blood–brain barrier endothelial cells. Issue 10 (18th June 2017) - Lee, Seon-Bong; Kim, Ju-Hyeong; Cho, Myung-Haing; Choe, Eun-Sang; Kim, Kwang-Sik; Shim, Soon-Mi
ABSTRACT: The purpose of the current study was to investigate the effect of two commercial cigarette smoke condensates (CCSC) on oxidative stress and cell cytotoxicity in human brain (T98G) or astrocytes (U-373 MG) in the presence of human brain microvascular endothelial cells (HBMEC). Cell viability of mono-culture of T98G or U-373 MG was markedly decreased in a concentration-dependent manner, and T98G was more susceptible than U-373 MG to CCSC exposure. Cytotoxicity was less prominent when T98G was co-cultured with HBMEC than when T98G was co-cultured with U-373 MG. Significant reduction in trans-epithelial electric resistance (TEER), a biomarker of cellular integrity was noted in HBMEC co-cultured with T98G (HBMEC-T98G co-culture) and U-373 MG co-cultured with T98G (U-373 MG-T98G co-culture) after 24 or 48 hr CCSC exposure, respectively. TEER value of U-373 MG co-cultured with T98G (79–84%) was higher than HBMEC co-cultured with T98G (62–63%) within 120-hr incubation with CCSC. Reactive oxygen species (ROS) generated by CCSC in mono-culture of T98G and U-373 MG reached highest levels at 4 and 16 mg/ml, respectively. ROS production by T98G fell when co-cultured with HBMEC or U-373MG. These findings suggest that adverse consequences of CCSC treatment on brain cells may be protected by blood–brain barrier or astrocytes, but with chronic exposure toxicity may be worsened due to destruction of cellular integrity.